Treatment of Inter-MitraClip Regurgitation Due to Posterior Leaflet Cleft by Use of The Amplatzer Vascular Plug II device - Mantri, Neha M.; Singh, Gagan D.; Smith, Thomas; Rogers, Jason H. (Cardiology and Cardiovascular Medicine, 2017)
Abstract not available in the source database.